Penerapan Media Presentasi Interaktif Matakuliah Fisika Terapan Pada Taruna Akademi Maritim Indonesia Aipi Makassar - Agriani Pongkessu; Muhammad Hatta; Hernita Arifuddin; Ismail Ismail (Journal on Education, 2023)
Research and implementation has been carried out which aims to determine the profile of interactive presentation media for cadets at the Indonesian Maritime Academy AIPI Makassar which is valid, determine of the lecturer's assessment of the applied presentation media, determine the cadets' response to the applied presentation media. The developed media was validated by two experts consisting of material experts and applied experts. The sample in this study consisted of practitioners who were Applied Physics lecturers as many as 2 people and second semester of cadets at the Indonesian Maritime Academy AIPI, totaling 35 Cadets. The development procedure uses the four-D (4-D) model which consists of defining, designing, and developing stages. The defining stage includes beginning-end analysis, learner analysis, concept analysis, goal specification. The design stage includes media selection, initial design. At the development stage, validation by experts was carried out and revised so as to obtain results that were suitable for use. The results showed that the interactive presentation media and learning tools for Applied Physics courses developed were declared valid so that they were feasible to use in the RPS, the lecturer's assessment of interactive presentation media showed that both practitioners agreed that the media developed was feasible to use and met the indicators related to media assessment, students' responses to interactive presentation media obtained very good responses